Editors' Word - Ejdus, Filip; Kovačević, Marko; Vujinović, Nikola (Journal of Regional Security, 2018)
This issue of JRS in most part resulted from academic sessions of the Belgrade Security Forum held in September 2012. The aim of the Forum was to bring academic and policy communities from the field of regional peace-building together in order to widen and deepen the knowledge and practice of security community building. In addition to studying how policy and academic security communities of practice overlap into constellations of practices, the Belgrade Security Forum aimed to build one such constellation. Articles in this issue cover various aspects of security practices, intersecting with different institutional and regional settings to illustrate the validity of this theoretical framework in analyzing international security phenomena.